PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERKEBUNAN NUSANTARA V UNIT PKS TERANTAM - Simbolon Jelita Reta; Zulfadil Zulfadil; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of training and work discipline onemployee performance at PT. Perkebunan Nusantara V PKS Unit Terantam. Thepopulation in this study were all employees at PTPN V PKS Terantam Unit,amounting to 100 people. The sampling method in this study was purposivesampling technique, namely by selecting respondents. According to Sugiyono(2018:138) purposive sampling is a sampling technique with certainconsiderations. The sample in this study was 50 employees who worked at PTPNV PKS Terantam Unit. Primary data was collected by using a questionnaire as aninstrument to prove the results of the study, to test the hypothesis in this studyusing the instrument test, classical assumption test, multiple linear regressionanalysis, and hypothesis testing with the help of the SPSS program. The samplingtechnique that has been selected is simple random sampling technique. The resultsof the study show that: 1) Training partially has a significant effect on employeeperformance. 2) Work discipline partially has effect but not significant onemployee performance. So it is necessary to have work discipline to have apositive influence on employee performance. This shows that the better theapplication of work discipline, the better the employee's performance will be. 3)Training and work discipline simultaneously have a significant effect on employeeperformance Keywords: Training, Work Discipline, Employee Performance